Efficacy and safety of bivalirudin in coronary artery disease patients with mild to moderate chronic kidney disease: Meta-analysis. Issue 5 (May 2018) - Zeng, Xiaofang; Lincoff, A. Michael; Schulz-Schüpke, Stefanie; Steg, Philippe Gabriel; Elbez, Yedid; Mehran, Roxana; Stone, Gregg W.; McAndrew, Thomas; Lin, Jianhui; Zhang, Xindan; Shi, Wenhai; Lei, Han; et al.
Highlights: Impaired renal function does not influence the safety profile of bivalirudin. Bivalirudin is suitable for cardiovascular disease patients with renal insufficiency. The use of bivalirudin decreases bleeding events more than heparin plus glycoprotein IIb/IIIa inhibitors (GPIs). Similar ischemic events were observed between bivalirudin and heparin plus GPIs. Abstract: Background: Patients with chronic kidney disease (CKD) have elevated bleeding and ischemic outcomes. We aim to assess the short- and long-term efficacy and safety of bivalirudin compared to heparin plus glycoprotein IIb/IIIa inhibitors (GPIs) in coronary artery disease (CAD) patients with CKD. Methods: Randomized trials were searched in PubMed, Cochrane, and Embase databases up to January 2017. Among the trials retrieved, efficacy endpoints were defined as mortality, myocardial infarction (MI), repeat revascularization, stent thrombosis, and major adverse cardiac events (MACEs). Safety endpoints were reported as non-coronary artery bypass grafting (CABG) related major bleeding and thrombolysis in myocardial infarction (TIMI) major bleeding. Risk ratio (RR) and 95% confidence interval (CI) were calculated for each outcome using a fixed effect model. Results: Five studies with a total of 3796 patients were included. In short-term follow up (30 days), bivalirudin significantly reduced non-CABG related major bleeding ( p  = 0.0004) and TIMI major bleeding ( p  = 0.007) compared to heparin plus GPIs. No significant differences were observed in rates of mortality, MI, repeat revascularization, stent thrombosis, and MACEs between the two groups in short- and long-term follow up (6 months to 3 years). In patients with ST elevated myocardial infarction (STEMI) with concurrent CKD, the decreased non-CABG related major bleeding ( p  = 0.04) without increasing ischemic events was also observed after short-term follow up. Conclusions: (1) Bivalirudin is safer than and as effective as heparin plus GPIs in CAD patients with CKD. (2) Impaired renal function does not affect the safety benefits of bivalirudin. (3) Similar efficacy profiles were identified between the two groups after both short- and long-term follow up in the CAD patients with CKD.